PERILAKU BELAJAR MAHASISWA PROGRAM STUDI PGSD DALAM MENGIKUTI PERKULIAHAN (Studi Deskriptif Kuantitatif: pada Program Studi PGSD FKIP UNIPAS MOROTAI) - Irawati Sabban (Universitas Khairun, 2017)
This research is aims to find out the empirical evidence dealing with learning conduct of college students of PGSD study program University of Pasifik Morotai in following the lecture. This is quantitative descriptive research. Sampling techinique of this research is probablity sampling by simple rendom sampling with the result that be gained amount 30 college students . Data analysis technique uses one sample t-test college students of PGSD Unipas Morotai in following the lecture still poor, the highest number is 65% of being expected to be accepted. Key word: Learning conduct. College students, Lecture